Portage: A Modular Data Remap Library for Multiphysics Applications on Advanced Architectures. (28th September 2021) - Herring, Angela; Ferenbaugh, Charles; Malone, Christopher; Shevitz, Daniel; Kikinzon, Evgeny; Dilts, Gary; Rakotoarivelo, Hoby; Velechovsky, Jan; Lipnikov, Konstantin; Ray, Navamita; Garimella, Rao
Portage is a scalable and extensible remap library for numerical simulations. It supports state-of-the-art remap schemes for meshes and particles in 2D and 3D up to a second-order accuracy.Portage ensures critical properties such as local/global conservation and bounds preservation for mesh remap. It enables multi-material field remap through a dedicated plugin, and leverages the hybrid parallelism exposed by advanced architectures using multi-processing and multi-threading.